2019
DOI: 10.15537/smj.2019.8.24411
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ADAM33 gene’s single nucleotide polymorphism variants against asthma and the unique pattern of inheritance in Northern and Central Punjab, Pakistan

Abstract: Objectives: To investigate the relationship of 3 single nucleotide polymorphism (SNP) variants of ADAM33 with asthma susceptibility in patients from Northern and Central Punjab, Punjab, Pakistan. Methods: In this case-control study, healthy and asthmatic participants were recruited between 2015 and 2017. The SNPs of ADAM33 gene, rs2280089, rs2280090, and rs2280091 were analyzed in 296 asthma patients and 343 healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The different studies, especially GWAS, have identified several genomic variants in asthma-susceptible genes which are associated with disease and regulate the expression of their corresponding genes (Naeem, 2022;Sabar et al, 2018Sabar et al, , 2020. Several genomic variants have been reported as highly significant in GWAS in large cohorts but lack similar association in replica studies on different ethnicities which are driving forces for researchers to find the true diagnostic and prognostic markers in different ethnic populations (Ghani et al, 2017(Ghani et al, , 2019a.…”
Section: Discussionmentioning
confidence: 99%
“…The different studies, especially GWAS, have identified several genomic variants in asthma-susceptible genes which are associated with disease and regulate the expression of their corresponding genes (Naeem, 2022;Sabar et al, 2018Sabar et al, , 2020. Several genomic variants have been reported as highly significant in GWAS in large cohorts but lack similar association in replica studies on different ethnicities which are driving forces for researchers to find the true diagnostic and prognostic markers in different ethnic populations (Ghani et al, 2017(Ghani et al, , 2019a.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Asthma is considered to be a complex genetic syndrome resulting from the interplay of various genes and environmental factors. 6 During last ten years different studies have been performed to identify association of different genes with atopy and asthma related phenotypes globally across various populations [8][9][10][11][12][13][14][15] which reveal that more than 100 genes are responsible for asthma pathogenesis 16 . Transforming growth factor-β (TGF-β) superfamily is an important group of ligands responsible for alveolarization, recruitment of immune cells, endothelial and epithelial barrier functions, platelet aggregation, cell proliferation and differentiation, apoptosis and other biological pathways within the airway.…”
Section: Introductionmentioning
confidence: 99%